Re-visiting car guarding as a livelihood in the informal sector. Issue 5 (3rd September 2021) - Foster, John; Chasomeris, Mihalis; Blaauw, Derick
ABSTRACT: This study aims to examine how car guarding remains a sustainable means of livelihood in the informal sector. The study interviewed 30 car guards at six different locations in Durban, South Africa. It examined their demographic characteristics, income, education and skills, among other factors. Furthermore, it compares the findings from 2019 with the 2015 findings from Foster and Chasomeris (2017, Examining car guarding as a livelihood in the informal sector. Local Economy 32(6), 525–538. https://doi.org/10.1177/0269094217727990). The findings show deterioration in the real income levels and livelihoods. In 2015, 22 car guards earned above a domestic worker's minimum hourly wage of ZAR15, compared to 16 car guards in 2019 and, only eight above the national minimum wage of ZAR20 per hour. There is a notable decline in expenditure on accommodation and reduced optimism about their future. Car guards still display a level of entrepreneurship, especially where daily bay fees are not paid to car guarding agents.